PENERAPAN MODEL COOPERATIVE LEARNING TIPE SCRAMBLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS KELAS VI SEMESTER II SDN 1 PUTAT GROBOGAN - Hartoyo Hartoyo (Program Studi Pendidikan Guru Sekolah Dasar, 2019)
This study aims to improve the ability of social studies learning outcomes in social studies learning in class VI SD Negeri 1 Putat through learning models Value Clarification Technique. This research is a classroom action research where researchers collaborate with colleagues as observers in conducting research. The research subjects were class VI SD Negeri 1 Putat students, as many as 20 students consisted of 14 male students and 6 female students. Learning outcomes of class VI students on social studies subjects increased from each action in each cycle, increasing student learning outcomes in class VI students from the results of the evaluation of the first cycle of students who completed as many as 14 people (70%), in the second cycle to 19 people (95 %). This is evident from the results of evaluations of students who completed the KKM value of the total number of students as many as 20 people the results increased. Conclusion The use of scramble type cooperative learning model can improve the ability of social studies learning outcomes in social studies learning class VI SD Negeri 1 Putat.